Chromenopyridin A, a new N-methoxy-1-pyridone alkaloid from the endophytic fungus Penicillium nothofagi P-6 isolated from the critically endangered conifer Abies beshanzuensis. Issue 8 (18th April 2022) - Zhu, Yuan-Xing; Peng, Cheng; Ding, Wenxin; Hu, Jin-Feng; Li, Jiyang
Abstract: A new N -methoxy-1-pyridone alkaloid [chromenopyridin A (1 )] and four known compounds (2 –5 ) were isolated and identified from the endophytic fungus Penicillium nothofagi P-6, which was derived from the bark of the critically endangered conifer Abies beshanzuensis . Their structures were elucidated by extensive spectroscopic analyses and single-crystal X-ray diffraction. Among the isolates, compound 1 showed considerable cytotoxicities against the A549 and Hela human cancer cell lines, with IC50 values of 14.7 and 11.3 μM. In addition, compounds 1 and 4 exhibited potent antibacterial activity against Staphylococcus aureus with MIC values of 62.5 and 15.6 μg/mL, respectively. Graphical Abstract: